2017
DOI: 10.1016/j.burns.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated re-epithelialization of partial-thickness skin wounds by a topical betulin gel: Results of a randomized phase III clinical trials program

Abstract: The clinical significance of timely re-epithelialization is obvious in burn care, since delayed wound closure is enhancing the risk of wound site infection and extensive scarring. Topical treatments that accelerate wound healing are urgently needed to reduce these sequelae. Evidence from preliminary studies suggests that betulin can accelerate the healing of different types of wounds, including second degree burns and split-thickness skin graft wounds. The goal of this combined study program consisting of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…Betulin is isolated from birch bark, and in vitro studies of human keratinocytes demonstrate that betulin enhances keratinocyte migration and upregulation of pro-inflammatory cytokines, such as IL-6, IL-8, and COX-2 [102]. Two parallel clinical phase III studies demonstrated accelerated wound closure following topical treatment with a betulin gel in split-thickness skin graft donor sites (NCT01807650 and NCT01657305) [103].…”
Section: Non-endogenous Moleculesmentioning
confidence: 99%
“…Betulin is isolated from birch bark, and in vitro studies of human keratinocytes demonstrate that betulin enhances keratinocyte migration and upregulation of pro-inflammatory cytokines, such as IL-6, IL-8, and COX-2 [102]. Two parallel clinical phase III studies demonstrated accelerated wound closure following topical treatment with a betulin gel in split-thickness skin graft donor sites (NCT01807650 and NCT01657305) [103].…”
Section: Non-endogenous Moleculesmentioning
confidence: 99%
“…In the Phase 3 setting, Oleogel‐S10 was found to accelerate wound healing in partial thickness wounds in split thickness skin graft (STSG) donor site wounds (studies BSH‐12 and BSG‐12) (Barret et al, ), and in Grade 2a burn wounds (BBW‐11) (Frew et al, ). In STSG donor site wounds, the 17‐day healing period with standard treatment was reduced by 1–2 days (Barret et al, ). In Grade 2a burn wounds, the 9‐day healing period with standard treatment was reduced by 1 day (Frew et al, ).…”
Section: Oleogel‐s10: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…Numerous studies have reported on its effectiveness in the treatment of EB wounds and other skin lesions, e.g. after laser procedures (19)(20)(21)(22). It is the first registered drug containing a formula based on triterpene compounds from birch bark.…”
Section: Discussionmentioning
confidence: 99%